(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role of modern pedagogical technologies in ensuring the cognitive development of schoolchildren. The theoretical foundations of cognitive development, including classical psychological approaches and modern innovative methods, are highlighted, as well as ways to develop students’ cognitive activity. The results of the study show that modern pedagogical technologies are effective in developing students’ thinking, independent thinking, and problem-solving skills.